Freshwater fish larval rearing system - Mukai, Yukinori (2010)
Summary of the Invention The present invention provides a system and method for rearing freshwater fish such as sutchi catfish and African catfish or the like, which is capable of reducing cannibalistic activities among the fish. In the system, a safe and conducive place for young fish to grow is provided. The fish kept in the system have shown that the tendency among the fish to attack and cannibalize other fish is reduced. According to the present invention, the system includes a first water tank for rearing larvae or young fish and a second water tank for culturing phytoplankton. The first tank is kept under a dark condition and the second tank is exposed to the light either artificial or natural light such as sunlight. The tank for growing phytoplankton is aerated for promoting its growth. Water containing the phytoplankton is supplied to the first water tank as food for the fish. The water also provides a conducive environment for freshwater fish. At least a pump is provided in the system for circulating the water from the first water tank to the second water tank and vice versa. It is an object of the present invention to provide a system and method for rearing freshwater fish such as sutchi catfish and African catfish or the like, which is capable of reducing cannibalistic activities among the fish. It is also another objective of the present invention to promote the physical growth of the fish during rearing.